Foreign Direct Investment, Governance, and the Environment in China Regional Dimensions - Zhang, J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book links the environment and corruption with China's large inflows of foreign direct investment (FDI). It investigates the effects of economic development and foreign investment on pollution in China; the effects of corruption and governance quality on FDI location choice in China.
Keywords: Environmental policy; Asia—Economic conditions; Environmental economics; Development economics; Regional economics; Spatial economics; Economic growth; Environmental Politics; Asian Economics; Environmental Economics; Development Economics; Regional/Spatial Science; Economic Growth